Comparison of physiological and physical demands between small-sided games and official matches in youth football players - Carril-Valdó, J. J.; Ferrandis, J.; Claver, F.; Gil-Arias, A.; González-Rodenas, J. (European Journal of Applied Physiology, 2025)
Purpose This study aimed to compare the physiological and physical demands between two spatial formats of small-sided games (SSGs) and competitive matches in youth football players.